Social origins, cognitive ability, educational attainment and social class position in Britain: A birth cohort and life-course perspective - Bukodi, E; Bourne, M; Betthäuser, B; Goldthorpe, J (2019)
The aim of this Summary Report is to show how social origins, when viewed in a comprehensive, multidimensional way, affect the educational and labour market attainments of individuals whose cognitive ability at a relatively early stage in their educational histories is at a similar level.